Analisis HPP Menggunakan Metode Full Costing Untuk UMKM Eni Bubur Dan Finarak ByAulianisak Untuk Menentukan Harga Jual - Silvi Salsabila Cahyani; Rochmad Bayu Utomo (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
For UMKM Eni Bubur and Finarak by Aulianisak are still inaccurate in determining the selling price because it does not cover all production costs, only the basic ingredients, so unclear losses often occur. So this research aims to analyze the methods used by UMKM with a more accurate full costing method, namely using a descriptive method using interviews, observation and documentation of UMKM owners. This gives results if there are differences between the full costing method and the UMKM method, so it can be concluded that the full costing method is more accurate.